Differential effects of positive and negative upper airway pressure application on atrial electrophysiology: implications for CPAP-therapy in OSA-patients. (19th May 2022) - Linz, B; Hertel, JN; Tfelt-Hansen, J; Jespersen, T; Linz, D
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Novo nordisk foundation Background: Obstructive sleep apnea (OSA) is closely associated with atrial fibrillation (AF) and OSA-treatment by continuous positive airway pressure (CPAP) is believed to reduce the AF burden in OSA-patients. While negative upper airway pressure during obstructive respiratory events have been shown to increase AF susceptibility, atrial electrophysiological effects of positive upper airway pressure during CPAP-therapy are unknown. Purpose: In pigs, we investigated differential atrial electrophysiological effects of increasing levels of CPAP-applications compared to obstructive respiratory events. Methods: In sedated and spontaneously breathing pigs, obstructive respiratory events were simulated by intermittent negative upper airway pressure (INAP) applied via a pressure device connected to the intubation tube. INAP was applied for 75 seconds with a 10 minute resting period in-between. After four INAP-applications, during which atrial electrophysiological responses to INAP were recorded, continuous positive airway pressure was applied in increasing pressure stages for a duration of 20 minutes for each pressure level (4, 8, 12 and 16 mbar). Atrial effective refractory periods (AERP) were recorded at the free wall of the right atrium (RA) and in the distal area of the coronary sinus (CS) before (Pre-INAP), during (INAP) and after (Post-) INAP and every 10 minutes throughout the stepwise increase of CPAP. Results: AERP shortened due to INAP application in the RA (Pre-INAP 134±7ms vs. INAP 95±7ms; p=0.008, Fig.1.), but not in the CS (Pre-INAP 132±8ms vs. INAP 110±9ms; p=0.144, Fig.2). Stepwise increases of CPAP-application up until 12 mbar did neither result in changes of RA- nor CS-AERP. Only CPAP-application at 16 mbar (CPAP16) resulted in transiently shortened CS-AERP (CPAP-baseline 140±6ms versus CPAP16 115±10ms; p=0.0081, Fig.2.), but not RA-AERPs (p=0.31, Fig.1.). Conclusion: While simulation of obstructive respiratory events by INAP were reproducibly associated with a predominantly right atrial shortening of refractoriness, high-pressure CPAP-application of 16 mbar was associated with an isolated moderate shortening of left atrial refractoriness. These findings may have important implications for CPAP treatment in patients with AF, which should be considered in the design of future clinical studies.